Effect of graphene on properties of acrylic emulsion intumescent fire retardant coating - Mac Van Phuc,; Dao Phi Hung,; Nguyen Anh Hiep,; Nguyen Thien Vuong,; Trinh Van Thanh, (Vietnam Journal of Science and Technology, 2024)
Nowadays, intumescent paint is one of the most popular fireproof paint products and is widely used in buildings. They can be applied to steel, wood, concrete, etc. This study aimed to enhance the properties of intumescent coating by graphene addition. The effect of graphene (GR) content on fire resistance, thermal and mechanical properties of water-based intumescent coatings were studied. Intumescent coating formulations include acrylic emulsion binder (R4152), flame retardant additives (Ammonium polyphosphate (APP) - acid source, pentaerythritol (PER) - carbon source, melamine (MEL) - foaming source), fire retardant fillers (TiO2, Al(OH)3) were prepared by mixing different graphene content (0.5, 1, 1.5 and 2 wt.% GR). The investigated coating properties were examined by fire protection test, furnace test, static water immersion test, scanning electron microscopy (SEM), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and mechanical properties (adhesion, pendulum hardness). The results showed that the GR could effectively enhance the fire resistance performance (from 13.6 % to 23.4 %), thermal stability (from 2.9 % to 5.2 %), water resistance (from 5.0 % to 11.9 %), and mechanical properties (from  5 % to 12 %) of the coating.